Fabrication of black-gold coatings by glancing angle deposition with sputtering - Vitrey, Alan (Beilstein J Nanotechnol, 2017)
The fabrication of black-gold coatings using sputtering is reported here. Glancing angle deposition with a rotating substrate is needed to obtain vertical nanostructures. Enhanced light absorption is obtained in the samples prepared in the ballistic regime with high tilt angles. Under these conditions the diameter distribution of the nanostructures is centered at about 60 nm and the standard deviation is large enough to obtain black-metal behavior in the visible range.